Eficiência dos gastos nas universidades federais brasileiras: uma proposta para a Universidade Federal de Goiás - Silva, Aretuza Pereira (2018)
The objective of this study was to measure the efficiency of the Brazilian Federal Universities' expenditures to identify the Benchmark Universities and, from this information, propose more efficient resource application measures for the Universidade Federal de Goiás (UFG). For this purpose, the Data Envelopment Analysis (DEA) was used, a non-parametric methodology that allows comparative analysis of the efficiency of the Federal Institutions of Higher Education (IFES). In order to measure the efficiency of expenditures in Federal Universities, data from the Censo de Educação Superior of INEP and data from the Ranking Universitário Folha (RUF) were used. A diagnosis was made to identify the level of efficiency of the Benchmark Universities, in which the results indicate that the following IFES have obtained the best levels of efficiency: UFPB, UFPA, UFRGS, UFAL, UFSJ, UFMA and UFF. It was verified that the UFG was among the relatively inefficient Federal Universities in the period from 2012 to 2015. From this information four measures were proposed to improve the performance indicators of the UFG, which are: (a) to reduce the number of courses offered; (b) reduce school dropout rates; (w); increase the number of vacancies in undergraduate courses; (d) improve results in the RUF Ranking.